Evaluation of Lentil Varieties/Lines for Utilization of Rice Fallow in Tripura - Yadav, Gulab Singh; Datta, M.; Saha, Poulami; Debbarma, Chiranjit (Indian Journal of Hill Farming, 2016)
A field experiment was conducted during 2013-14 and 2014-15 to evaluate the performance of lentil varieties under reduced tillage condition in rice fallow. Seventeen lentil (Lens culinaris) varieties/lines were tested in rice fallow under reduced tillage condition with residual soil moisture. Results revealed that the varieties/lines, L-112-7 and ILL-237 took minimum number of days (52-54 days), however, ILL-10971 took maximum number of days (67-69 days) for 50% flowering. Variety L-112-7 was matured 85-89 days after sowing, while ILL-10971 required maximum number of days (99-103 DAS) for 50% pod maturity. RL-12-171 was recorded maximum root length and nodule number/plant followed by L-112-7, BM-5 and ILL-10951, while lowest root length and minimum number of nodule/plant was found in ILL-10971. Root length and nodule number/plant were showed a significant linear relationship with seed yield. The highest numbers of branches/plant were recorded with ILL-10951 (9.9) in 2013-14 and RL-12-171 (8.6) in 2014-15. The maximum number of pods/plant was recorded with L-4076 (118.7) in 2013-14 and ILL-10951 (87) in 2014-15. Number of seeds/pod was the highest in WBL-81 (2.0). The test weight (weight of 1000 seed) was recorded to be highest in ILL-8180 (69.0-70.0) followed by ILL-10897 (55.0-56.0). The highest seed yield was recorded in RL-12-171 followed by L-112-7 and ILL-10951, all of which were significantly higher than those of other cultivars. Most of the cultivars matured in about 100 days with very few maturing in about 110 days. Thus, the study revealed the opportunity of lentil cultivation in lowland rice fallow with appropriate technologies in Tripura. Therefore, lentil is a potential crop for crop diversification and enhancing productivity of rice based cropping systems in Tripura.